TANGGUNG JAWAB HUKUM BADAN USAHA PELABUHAN TERHADAP KLAIM ATAS KELALAIAN PELAYANAN JASA BONGKAR MUAT BARANG KEPADA EKSPEDITUR - Duyo, Muhammad Rafiq Abdillah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research is aimed to analyse legal consequences of port enterprise regarding claim over negligence in loading and uploading services to expeditor to investigate how the responsibility is performed by PT. Pelabuhan Indonesia IV regarding the claim over negligence in loading and uploading services to the expeditor and what measures are taken by the port enterprise to settle the dispute. This is an empirical legal research that employed socio-juridical approach. Primary data was obtained by conducting interviews and observation, while the secondary data from library research that relevantly supports the issue observed. All those types of data will be analysed with descriptive and qualitative methods. The research result reveals that the implementation of the responsibility of PT. Pelabuhan Indonesia IV is restricted by law. As implied in Article 468 Paragraph (2), if the port enterprise could provide proof of being not guilty, in which the goods are damaged when shipped or forwarding, this damage is not the responsibility of PT. Pelabuhan Indonesia IV. The claim can be responded through non-litigation process in which negotiation may take place between two involved parties.